2008
DOI: 10.1002/job.540
|View full text |Cite
|
Sign up to set email alerts
|

Conflict management between and within teams for trusting relationships and performance in China

Abstract: SummaryTrusting relationships are increasingly considered vital for making teams productive. We propose that cooperative management of conflict can help team members to be convinced that their teammates are trustworthy. Results from 102 organizations in China support the theorizing that how teams to manage conflict with each other affects within-team conflict management. Specifically, cooperative conflict between teams helps teams to manage their internal conflicts cooperatively that strengthens trust that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 109 publications
2
140
0
3
Order By: Relevance
“…Previous literature has provided empirical support for the merits of conflict management in organizational work teams (e.g., Alper, Tjosvold, & Law, 2000;Hempel, Zhang, & Tjosvold, 2009), demonstrating that teams performed better when they endorsed a more constructive approach towards conflict rather than a destructive approach. As we found that steeper status hierarchies reduce process and task conflicts when teams perform tasks of low complexity, we expect that such constructive strategies may be less relevant under these circumstances.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Previous literature has provided empirical support for the merits of conflict management in organizational work teams (e.g., Alper, Tjosvold, & Law, 2000;Hempel, Zhang, & Tjosvold, 2009), demonstrating that teams performed better when they endorsed a more constructive approach towards conflict rather than a destructive approach. As we found that steeper status hierarchies reduce process and task conflicts when teams perform tasks of low complexity, we expect that such constructive strategies may be less relevant under these circumstances.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…To test for mediation, which pertained to Hypotheses 2c, 3, 5, and 6c, direct and indirect effects in the SEM tests were calculated (Hempel, Zhang & Tjosvold, 2008;Zhang, Hempel, Han & Tjosvold, 2007) following relevant procedures in EQS that generated standard errors and path coefficients for these effects (Bentler, 2004). The indirect effect of employability on subjective career success was non-significant (β = -.09, ns), while the corresponding direct effect was found to be significant as per Hypothesis 2b (β = .32, p < .01).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…In this sense, to the extent that the managers can engender positive perceptions in the ERs-that is, ERs being able, benevolent and of integrity-a trusting relationship is more likely to take place (Fulmer and Gelfand 2012). Developing a trusting re-lationship is essential to be able to understand organizational dynamics as well as promoting organizational productivity and team performance (Hempel et al 2009). …”
Section: Discussion On Expectations Of Spanish Employers On Ers' Rolementioning
confidence: 99%